Kepastian Hukum Perkawinan Beda Agama dalam Surat Edaran Mahkamah Agung Nomor 2 Tahun 2023 - Alfikri, Ahmad Faiz Shobir; Izzuddin, Ahmad (MAHAKIM Journal of Islamic Family Law, 2024)
Supreme Court Circular Letter (SEMA) No. 2 of 2023 contains the latest regulation on interfaith marriage. This study examines the legal position of SEMA No. 2 of 2023 from juridical, sociological, and philosophical perspectives. In addition, this study also analyzes the application of SEMA No. 2 of 2023 based on the principle of legal certainty according to Gustav Radbruch. This research uses normative legal research methods with statutory and conceptual approaches. Data collection was conducted through a documentation study. The results showed that SEMA No. 2 Year 2023 is juridically recognized and has binding legal force based on Article 8 paragraph (1) of Law 12/2011 and Article 79 of the Supreme Court Law. Sociologically, SEMA No. 2 Year 2023 is following the social reality in the community. Philosophically, establishing SEMA No. 2 Year 2023 aims to create legal unity and certainty. However, the implementation of SEMA No. 2 Year 2023 is considered not optimal because it does not fulfill all aspects of the principle of legal certainty according to Gustav Radbruch. The aspects of legal certainty that are fulfilled in SEMA No. 2 Year 2023 include laws formulated based on facts and clarity in formulation. Meanwhile, the positive law aspect has been partially fulfilled, but the legal stability aspect, which requires the law not to be easily changed, has not been fulfilled. This research is expected to contribute to legal development in Indonesia, especially regarding interfaith marriages.